PEMBELAJARAN IPA BERBASIS LINGKUNGAN UNTUK SISWA SEKOLAH DASAR: SEBUAH KAJIAN LITERATUR - Cahyani, Christina Wahyu; Djudin, Tomo (STKIP Persada Khatulistiwa Sintang, 2024)
The environment actually has an important role in science learning in elementary schools. The environment can be in the form of the natural environment, social environment, or local culture as local wisdom. This article aims to find out the application, obstacles and benefits of environment-based science learning. The type of research in this paper is a literature study by analyzing various scientific articles. The data analysis technique uses the content analysis method. The results found that the application of environment-based science learning in elementary schools includes the use of modules, learning models, learning media and methods. Obstacles in implementing environment-based science learning in elementary schools include lack of training, limited time, ability to manage learning outside the classroom, low scientific literacy, and limited reading sources about science that are appropriate to the child's age. The benefits of implementing environment-based science learning in elementary schools include improving the quality of learning and student learning outcomes, making learning meaningful, increasing student awareness, curiosity and motivation.